A cross sectional study on nomophobia among medical students in Tirupati, Andhra Pradesh - Neelima, B. Yasoda; Kumari, J. Pavan; Pallavi, R. Sowmya; Sivakala, T.; Srinivas, K.; Prabhu, G. Ravi (International Journal Of Community Medicine And Public Health, 2023)
Background: Medical students are using more applications of smartphones in their course besides the primary purpose of communication. The excessive usage of smartphone has given rise to a condition known as “nomophobia”. The objectives of the study are to estimate the prevalence of nomophobia and to evaluate the determinants of nomophobia among participants. Methods: A cross-sectional study was conducted from July to August 2022 among 320 undergraduate medical students of Sri Venkateswara Medical College, Tirupati. NMP-Q questionnaire used as a tool for data collection. Ethical clearance was obtained from the Institutional Ethical Committee and informed consent was taken from the participant. Collected data was coded and entered into a Microsoft excel and analysed using statistical package for the social sciences (SPSS) software version 21.0. Results: Prevalence of nomophobia among study subjects was found to be 100% (320); of which 59% showed moderate nomophobia followed by mild (35%) and severe nomophobia (6%). Nearly 60% of the students are using smart phone for communication, 56% for entertainment and 46% for study purpose. Conclusions: All participants were suffering from nomophobia with different grades of severity. It was significantly associated with age, year of study, number of apps used, average time spent with mobile and messages sent per day. Most of them were using smart phone for communication, entertainment and study purpose.